2017
DOI: 10.1021/acs.biochem.7b00211
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Forkhead Domain of FOXA2 Bound to a Complete DNA Consensus Site

Abstract: FOXA2, a member of the forkhead family of transcription factors, plays essential roles in liver development and bile acid homeostasis. In this study, we report a 2.8 Å co-crystal structure of the FOXA2 DNA-binding domain (FOXA2-DBD) bound to a DNA duplex containing a forkhead consensus binding site (GTAAACA). FOXA2-DBD adopts the canonical winged-helix fold, with helix H3 and wing 1 regions mainly mediating the DNA recognition. Although the wing 2 region was not defined in the structure, isothermal titration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 48 publications
4
44
0
2
Order By: Relevance
“…1e). Therefore, and since crystallographic studies have demonstrated that actual DNA shape varies across Forkhead members 5,21 we decided to focus the analyses in the following sections on the DNA shape features, considering only the 1mer + shape models.…”
Section: Resultsmentioning
confidence: 99%
“…1e). Therefore, and since crystallographic studies have demonstrated that actual DNA shape varies across Forkhead members 5,21 we decided to focus the analyses in the following sections on the DNA shape features, considering only the 1mer + shape models.…”
Section: Resultsmentioning
confidence: 99%
“…Tridimensional modeling of the wild‐type and mutant FOXA2 DNA‐binding domains predicted conformational changes. These changes were predicted to modify the interaction between FOXA2 and DNA (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of the FOXA2 DNA‐binding domain (PDB ID 5X07) was obtained from the RCSB protein databank . The FOXA2 3D model was generated with Discovery Studio Visualizer software (Dassault Systemes BIOVIA, San Diego).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on protein structural predictions, all three variants are involved with DNA binding ability of FOXA2 (Boda et al, ). The p.R256S variant in our patient also occurs within the DNA‐binding domain (residues 157–258, [Li et al, ]); however, further functional studies are needed to determine whether the variant seen in this patient causes a dominant‐negative effect or haploinsufficiency.…”
Section: Discussionmentioning
confidence: 99%